2017
DOI: 10.1103/physrevlett.118.087002
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Laser-Controlled Competing Superconducting and Charge Orders

Abstract: We investigate the nonequilibrium dynamics of competing coexisting superconducting (SC) and charge-density wave (CDW) orders in an attractive Hubbard model. A time-periodic laser field A[over →](t) lifts the SC-CDW degeneracy, since the CDW couples linearly to the field (A[over →]), whereas SC couples in second order (A[over →]^{2}) due to gauge invariance. This leads to a striking resonance: When the photon energy is red detuned compared to the equilibrium single-particle energy gap, CDW is enhanced and SC is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 42 publications
4
94
0
Order By: Relevance
“…The differences may derive from more complex physics including amplitude fluctuations, lattice distortion, 14,23 or competing charge order. 25,27 We have also demonstrated that admixing higher harmonics in the driving operation can result in an additional enhancement of the c-axis transport. This observation opens the door towards optimal control of superconductivity via optical driving, by combining several higher harmonics.…”
Section: Bilayer Josephson Junctionsmentioning
confidence: 73%
See 2 more Smart Citations
“…The differences may derive from more complex physics including amplitude fluctuations, lattice distortion, 14,23 or competing charge order. 25,27 We have also demonstrated that admixing higher harmonics in the driving operation can result in an additional enhancement of the c-axis transport. This observation opens the door towards optimal control of superconductivity via optical driving, by combining several higher harmonics.…”
Section: Bilayer Josephson Junctionsmentioning
confidence: 73%
“…56 These discrepancies may arise due to physics that is not included in our simulation such as finite temperature effects, amplitude fluctuations of the order parameter, nonlinear lattice distortion, 14,23 and competing orders. 25,27 V. CONCLUSIONS…”
Section: Bilayer Josephson Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of the general relation (49) is that the computation of the nonlinear optical kernel K(ω) within a specific and controlled approximation allows one to address separately the various physical processes relevant for each system, and to test the results against the experiments. This approach can lead to a considerable advantage in the case of collective electronic modes across a phase transition, when the full numerical solution of a time-dependent problem is computationally challenging [19][20][21][22][23][24][25][26][27][28] , and does not always allow one to disentangle the contributions from different excitations channels. This is exactly what happens for the 2∆ oscillations in a superconductor, that have been ascribed so far either to the excitation of densitylike fluctuations 14 or to the Higgs mode [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…This model describing CDW and SC order [40,50,51] and its experimental realizations in cold atom systems has recently shed new light on the dynamics of charge and spin fluctuations [52][53][54][55].…”
Section: Model and Formalismmentioning
confidence: 99%